ANALYSIS OF BUSINESS DEVELOPMENT STRATEGY AT DHINDA BEAUTY CLINIC - Laras Ratu Khalida; Syifa Pramudita Faddila; Dexi Triadinda (PT. Berkah Digital Teknologi, 2025)
Research method— The research employs a qualitative approach, utilizing surveys and interviews to gather data on current beauty standards as defined by women in Indonesia, alongside an analysis of the business’s internal and external environments through the SWOT framework. Result— The findings reveal that the current beauty standards among Indonesian women prioritize smooth skin (30.7%), well-dressed appearance (16.4%), and a glowing face (16.3%) according to the ZAP Beauty Index (2024). An effective business development strategy for Rumah Cantik Dhinda is proposed, emphasizing a combination strategy that includes market penetration to address promotional and marketing challenges, as well as addressing human resource needs by hiring additional employees. Conclusion— The study concludes that the integration of these strategies will enhance Rumah Cantik Dhinda’s market presence and operational effectiveness, providing a valuable reference for further research and practical application in business development courses within economics and management programs.on